الآراء النقدية لبدر شاكر السياب - عبيد، زينب علي (جامعة بابل - كلية التربية للعلوم الإنسانية, 2017)
عرف بدر شاكر السياب على أنه علامة بارزة في حركة الشعر العربي المعاصر بما حققه من إنجازات رائدة وإضافات بينه أغنت فعله الشعري بالأبداع وبالتجديد وامتدته بالحياة لفترة مديدة من الزمن، فان له تراثا نثريا من الخصوبة والثراء ما يجعله جديرا بالفخر والاعتزاز. فللسياب أفكار وتصورات ومفاهيم عن الواقع الشعري وتبدو أهمية هذه الأفكار والتصورات والمفاهيم في أن لها علاقة بالمشكلات المتعلقة بإنجازاته الإبداعية خاصة، وبالواقع الشعري والأدبي عامة، وبموقفه من شتي القضايا الفنية والفكرية التي تساهم في بلورة الكثير من جوانبها فلذلك اخترت موضوع (الآراء النقدية لبدر شاكر السيباب). أما تقسيم هذا العمل فيبتدأ أولا: أبرز المنابع الثقافية التي استقي منها السياب فنه، ثانيا: مفهوم التجديد عند السيباب. وثالثا: وظيفة الشعر، وربعا: الأسطورة والرمز في راي السياب، وخامسا: بعض آراء السياب في الشعر والشعراء.
We have learned from the tragedy of his life and the masterpieces of his poetry and his prose heritage, and what we learned most from Badr and his wonderful poetry. If Badr Shaker Al-Sayab is known as a milestone in the movement of contemporary Arabic poetry, with his achievements of pioneering and additions, he enriched his poetic work with creativity, innovation and life for a long period of time. He has a rich heritage of fertility and wealth which makes him worthy of pride. The ideas, perceptions and concepts about the poetic reality and the importance of these ideas, perceptions and concepts in relation to the problems related to his creative achievements, especially the poetic and literary reality in general, and his position on various artistic and intellectual issues that contribute to the crystallization of many aspects). And I have to show my division of this work: In the beginning I have prepared for this research Babars cultural sources, which derived from Sayab his art, and then dealt in the first topic: the concept of renewal at Sayab. In the second section: the function of poetry. And the third topic: the myth and the symbol in Ray Sayab, and the fourth topic: some views of Sayab in poetry and poets, and I hope that this work is admired.
Keywords: الشعر العربي -- الشعراء العرب -- نقد الشعر -- الدراسات النقدية -- السياب ، بدر شاكر -- التراجم -- العراق -- مستخلصات الأبحاث